Preliminary Results of the Effects of Spacings on the Growth and Yield of Tectona grandis Linn. F. - Adegbeihn, J. O. (Indian Forester, 1982)
This paper reports the effects of spacing on mean diameter, mean diameter of dominant trees, basal area, mean height, top height, form factor and total volume production of a 7 year old plantation of Tectona grandis (Teak) at Nimbla. The results show that whilst mean diameter, mean diameter of dominant trees and basal area production are significantly affected by spacing, mean height. Top height, form factor (overbark) and total volume production remain independent of the effect of this factor. Further more, there seems to be very little or no advntage to be gained by adopting spacings of either smaller or wider than 2.74 m by 183 m of 2.74 m By 3.66 m respectively.